2013
DOI: 10.1111/1467-9817.12019
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of fluency and reading comprehension in Spanish primary school children

Abstract: The importance of prosodic elements is recognised in most definitions of fluency. Although speed and accuracy have been typically considered the constituents of reading fluency, prosody is emerging as an additional component. The relevance of prosody in comprehension is increasingly recognised in the latest studies. The purpose of this research is to examine the contribution of prosodic reading to comprehension beyond automaticity in word reading, taking into account children's grade level. One hundred and twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
46
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 50 publications
9
46
0
7
Order By: Relevance
“…The mediating role of reading fluency appeared as soon as children became beginning readers in first-grade (Kim et al, 2012) and the relation between text reading fluency and reading comprehension remained stable from second- to fourth-grade (Kim & Wagner, 2015). In recent years, though, not only the child's ability to read a text quickly and accurately, but also their ability to read it with appropriate prosody (i.e., text reading prosody) has been found to be associated with reading comprehension (e.g., Benjamin & Schwanenflugel, 2010; Calet, Defior, & Gutiérrez-Palma, 2013; Miller & Schwanenflugel, 2006, 2008; Rasinski et al, 2009). Apart from correlations between text reading prosody and reading comprehension (e.g., Rasinski et al, 2009), studies also showed that text reading prosody accounted for substantial variance in reading comprehension, in addition to rate and accuracy (Klauda & Guthrie, 2008).…”
mentioning
confidence: 99%
“…The mediating role of reading fluency appeared as soon as children became beginning readers in first-grade (Kim et al, 2012) and the relation between text reading fluency and reading comprehension remained stable from second- to fourth-grade (Kim & Wagner, 2015). In recent years, though, not only the child's ability to read a text quickly and accurately, but also their ability to read it with appropriate prosody (i.e., text reading prosody) has been found to be associated with reading comprehension (e.g., Benjamin & Schwanenflugel, 2010; Calet, Defior, & Gutiérrez-Palma, 2013; Miller & Schwanenflugel, 2006, 2008; Rasinski et al, 2009). Apart from correlations between text reading prosody and reading comprehension (e.g., Rasinski et al, 2009), studies also showed that text reading prosody accounted for substantial variance in reading comprehension, in addition to rate and accuracy (Klauda & Guthrie, 2008).…”
mentioning
confidence: 99%
“…According to this, between the reading accuracy percentage and prosody there is a .50 relationship; and between reading accuracy percentage and reading speed there is a .40 significant relationship. Calet et al (2015) found significant positive correlations between the prosodic reading and the reading speeds in the second and fourth grades.…”
Section: The Relationship Between the Elements Of The Reading Fluencymentioning
confidence: 76%
“…Similarly, Rasinski, Rikli, and Johnston (2009) found a significant relationship between the reading out loud prosody of the third, fifth, and seventh grade students and their silent readings. Calet et al (2015) found significant positive relationships between reading comprehension in grade two and four and reading speed and prosodic reading. They also looked at the relationships between the elements of prosodic reading (sound, tonality, pauses, compartments of meaning units, and quality) and reading comprehension.…”
Section: Relations Between the Reading Comprehension And The Reading mentioning
confidence: 81%
See 1 more Smart Citation
“…읽기 자동성이란 인지적으로 많은 노력을 들이지 않 고 빠르고 정확하게 글을 읽을 수 있는 능력을 의미한다 (LaBerge & Samuels, 1974). 운율성에서는 문장을 구두점 또는 의미단위를 경계로 적절히 끊어 읽는지 (Kuhn, Schwanenflugel, & Meisinger, 2010;National Reading Panel, 2000), 평서문, 의문문 등의 문장유 형에 따라 적절한 음도변화를 주며 읽는지 (Calet, Gutiérrez-Palma, & Defior, 2015;Seo, 2016), 텍스트의 의미에 맞게 음량을 조절하며 읽는지 (Zutell & Rasinski, 1991) (Schwanenflugel, Hamilton, Kuhn, Wisenbaker, & Stahl, 2004 (Schwanenflugel et al, 2004;Yang, 2003 (Kuhn et al, 2010;National Reading Panel, 2000). (Calet et al, 2015;Kim, Park, & Kim, 2010;Kim & Pae, 2012;Kuhn & Stahl, 2003 (Kuhn & Stahl, 2003;Miller & Schwanenflugel, 2006;Schwanenflugel et al, 2004) (Kuhn & Stahl, 2003).…”
unclassified